2013
DOI: 10.1007/s10620-013-2944-y
|View full text |Cite
|
Sign up to set email alerts
|

The Day of the Week Does Not Affect the Adenoma Detection Rate

Abstract: ADR is not influenced by the day of the week in which a colonoscopy is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In mixed effects regression models in our research, ADR dropped significantly on Fridays and weekends compared to Monday, and the progressive decline trend of ADR was obvious. A similar phenomenon was shown in the cytotechnologists that the abnormal detection rates and screening speed would decreased in the later days of a week [22]. The well-known 'weekend effect' demonstrated that an admission to a hospital at weekends would show a higher mortality than others probably because of the poor medical care partly caused by the fatigue of medical staff [23,24].…”
Section: Discussionsupporting
confidence: 55%
“…In mixed effects regression models in our research, ADR dropped significantly on Fridays and weekends compared to Monday, and the progressive decline trend of ADR was obvious. A similar phenomenon was shown in the cytotechnologists that the abnormal detection rates and screening speed would decreased in the later days of a week [22]. The well-known 'weekend effect' demonstrated that an admission to a hospital at weekends would show a higher mortality than others probably because of the poor medical care partly caused by the fatigue of medical staff [23,24].…”
Section: Discussionsupporting
confidence: 55%
“…18 However, our finding of no substantial difference in reading performance by weekday is supported by other studies. 19,20 We found a seemingly lower crude sensitivity on Saturdays, but consider this finding to be due to random variations at certain small study sites and the small number of FN.…”
Section: Discussionmentioning
confidence: 71%
“…No variation between weekdays is demonstrated 138. In part, this is likely partially related to the bowel preparation quality 139…”
Section: The Standardsmentioning
confidence: 96%